The Impacts of (TADS) On International Trade, Economy and Public Health and Their Prevention and Control - Ayubi, Noor Mohammad (Journal of Natural Sciences – Kabul University, 2024)
Transboundary animal diseases (TADs) are importance in the international trade of animals and animal products. With rapidly increasing globalization the associated risk of transboundary diseases emergences is increased. They reduce production and productivity of affected animals disrupt local and national economies, and also threaten human health. Transboundary animal diseases are a concern globally, therefor cumulative effort is needed at international level to minimize the spread of infectious diseases across the borders. For most developing countries particularly eradication of most transboundary animal diseases is imposible due to a various technical, financial and logistical reasons. With development of the technology, livestock production has gained an important position in the national economy, socioeconomic development, poverty allevation and nutrition supply for human. Specific measures are required to safeguard the livestock industries from epidemics of infectious diseases and to up-hold safe international trade of livestock and their products.